Academic accommodation for post concussion student athletes: can physicians do better?. Issue 5 (11th March 2013) - Carson, James; Snow, Catherine; Lawrence, David; Kraft, Sari; Chatterjee, Ananda; MacKenzie, Heather; Moineddin, Rahim; Frémont, Pierre
Abstract : Objective: To determine the barriers and facilitators to the implementation of concussion related medical recommendations in a sport and school environment. Design: Retrospective longitudinal chart review and structured telephone interviews. Setting: A sport medicine physician's office in Ontario, Canada. Subjects: 159 students with a sport-related concussion. Intervention: The data collection involved a review of 170 charts of patients seen for concussion over a 5-year period (2006–2010). Two blinded authors independently reviewed each chart and SCAT or SCAT2 symptom self report form. In situations where there was discrepancy between the two reviewers results, a third author reviewed the charts. The telephone interviews supported the data collection. Outcome Measures: Our primary outcome measures were (1) whether the patient returned to their sport too soon, or before they had fully recovered, and (2) whether the patient returned to school too soon, or before they had adequately recovered. The phone interview was structured to collect outcome measures providing insight into the patients' post-concussion course and recovery process. This will assist in determining what factors they believe improved their condition, or what slowed the recovery process. Results: In terms of the primary outcomes, 43.53% of students returned to sport too soon and 44.71% returned to school too soon. Conclusions: Currently, physicians advise restricted mental and physical activity, but no clear guideline exists explaining exactly what cognitive rest entails for post-concussion student athletes. Efforts are needed to find the best method of implementing a coordinated plan for the post-concussion athlete who is returning to school. Competing interests: None.